2020
DOI: 10.3389/fpls.2020.00026
|View full text |Cite
|
Sign up to set email alerts
|

Response of Photosynthesis to High Growth Temperature Was Not Related to Leaf Anatomy Plasticity in Rice (Oryza sativa L.)

Abstract: Photosynthesis is highly sensitive to high temperature stress, and with the rising global temperature, it is meaningful to investigate the response of photosynthesis to growth temperature and its relationship with leaf anatomy plasticity. We planted 21 cultivars including eight indica cultivars, eight japonica cultivars, and five javanica cultivars in pot experiments under high growth temperature (HT, 38/28°C, day/night) and control treatment (CK, 30/28°C, day/night). Photosynthetic rate (A), stomatal conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This eventually leads to abscission, thereby affecting plant growth and productivity (Guo, Liu, et al, 2016; Gururani et al, 2015). Photosynthesis is one of the biological processes, which is significantly affected by HTS in rice plants (Yang et al, 2020). The optimum growth temperature for photosynthesis in rice plants is approximately 30°C and significantly decrease when temperature increases, resulting in the inhibitions of various redox and metabolic reactions taking place in PSII, PSI, cytochrome complex, and RuBisCo, that leads to decrease in photosynthetic rate (Yang et al, 2020; Yin et al, 2010).…”
Section: Drought and High Temperature Stresses: Effects And Response Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…This eventually leads to abscission, thereby affecting plant growth and productivity (Guo, Liu, et al, 2016; Gururani et al, 2015). Photosynthesis is one of the biological processes, which is significantly affected by HTS in rice plants (Yang et al, 2020). The optimum growth temperature for photosynthesis in rice plants is approximately 30°C and significantly decrease when temperature increases, resulting in the inhibitions of various redox and metabolic reactions taking place in PSII, PSI, cytochrome complex, and RuBisCo, that leads to decrease in photosynthetic rate (Yang et al, 2020; Yin et al, 2010).…”
Section: Drought and High Temperature Stresses: Effects And Response Mechanismsmentioning
confidence: 99%
“…Photosynthesis is one of the biological processes, which is significantly affected by HTS in rice plants (Yang et al, 2020). The optimum growth temperature for photosynthesis in rice plants is approximately 30°C and significantly decrease when temperature increases, resulting in the inhibitions of various redox and metabolic reactions taking place in PSII, PSI, cytochrome complex, and RuBisCo, that leads to decrease in photosynthetic rate (Yang et al, 2020; Yin et al, 2010). Studies performed by Yin et al (2010) showed that rice seedlings exposed to temperature higher than 35°C resulted in significant reduction of CO 2 assimilation under light and dark conditions, but was more sensitive under light.…”
Section: Drought and High Temperature Stresses: Effects And Response Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the subspecies adapt to different thermal regimes, the response of rice yield to temperatures varies with the subspecies. Indica and tropical japonica have higher heat resistance compared to temperate japonica (Shah et al., 2014; Yang et al., 2020). Despite the higher heat‐resistance of indica and tropical japonica , rice plants grown in the tropics and subtropics are frequently injured by high temperatures, most severe damage occurring during the booting and flowering stages, followed by the grain‐filling stage (Counce et al., 2005; Mohammed & Tarpley, 2009, 2010; Satake & Yoshida, 1978).…”
Section: Introductionmentioning
confidence: 99%